PENERAPAN STRATEGI BELAJAR PETA PIKIRAN (MIND MAP) DAN DIAGRAM ALIR (FLOW CHART) TERHADAP HASIL BELAJAR KIMIA SISWA SMA - Leny Sopia Latuny (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
One of the factors that impede student learning outcomes are not fully focused on in-depth understanding of the concept. This can be overcome by conducted activities in the laboratory. On the basis that in doing a study aimed at improving student learning outcomes using a mind map learning strategy and a flow diagram through direct instructional model material acid-base titration. The implementation in this study were pre-test-post-test nonequivalent group design Comparation. Subject of class XI High School Saint Agnes Surabaya. Data were analyzed quantitatively, the results showed that there were significant differences in learning outcomes between learning strategy and flow diagrams and mind maps. Conclusions of research that learning outcomes with this strategy mind map is higher than just using a strategy flow chart